Portfolio Optimization at Damascus Securities Exchange: A Fractal Analysis Approach - Kinda Dooba; Sulaiman Mouselli (Cogent Economics & Finance, 2023)
This paper adopts the fractal analysis approach, specifically a Hurst exponent index in portfolio optimization at the Damascus Securities Exchange (DSE). We construct three portfolios based on the Hurst index from stocks listed on the DSE during the period between 2019 and 2021 and find that these portfolios outperform the market portfolio in terms of returns, Sharpe ratio, Treynor ratio, and alpha. In addition, selecting stocks with high Hurst coefficients further enhances the performance of the portfolio. Importantly, even in out-of-sample tests, the three fractal portfolios continue to outperform the market portfolio. Furthermore, we find that fractal portfolios outperform portfolios formed using the momentum and size strategies demonstrating the superiority of the fractal analysis approach. We conclude that the incorporation of fractal analysis into the portfolio optimization problem allows the creation of a more efficient portfolio. Hence, we recommend that investors consider the Hurst exponent index in their portfolio optimization for better investment decisions.
Keywords: 330; Damascus Securities Exchange (DSE); fractal analysis; Hurst exponent; Long-Memory (LM) effect; market efficiency; Portfolio optimization